Diagnostic needle arthroscopy of the tarsocrural joint in standing sedated horses. Issue 3 (13th January 2020) - Kadic, Dimitri T. N.; Bonilla, Alvaro G.
Abstract: Objective: To develop and assess a needle arthroscopic technique to diagnose conditions of the tarsocrural joint (TCj) in standing sedated horses. Study design: Experimental study. Sample population: Six cadaveric hind limbs (phase 1) and six healthy horses (Phase 2). Methods: In phase 1, each TCj was examined with a 1.2‐mm‐needle arthroscope. Suitability of the needle arthroscope and degree of joint visualization with traditional arthroscopic approaches were assessed. In phase 2, the feasibility of the procedure was assessed in six standing healthy horses. A custom‐made splint and base were developed to maintain joint flexion during the procedure. Results: Thorough evaluation of the dorsal intra‐articular structures of the TCj via dorsomedial and dorsolateral approaches was possible in both phases. The procedure was feasible, quickly performed, and well tolerated by all horses. Complications consisted of moderate movement (2/6 horses) and hemarthrosis (3/6 horses). Conclusion: Diagnostic standing needle arthroscopy of the TCj allowed thorough evaluation of the dorsal aspect of the joint while avoiding the cost and risks associated with general anesthesia. Inadvertent puncture of the dorsomedial vasculature with the cannula and obturator led to significant hemarthrosis. Clinical impact: Needle arthroscopy of the TCj offers an alternative diagnostic tool when traditional imaging techniques (radiography and ultrasonography) are unrewarding or nondiagnostic. The technique is conceived mainly for diagnostic purposes, but its use during short interventions warrants investigation.